COVID-19: new scenario old problems: COVID 19 epidemic and hospital acquired infection - Auxilia, Francesco; Maraschini, Anna; Bono, Patrizia; Ungaro, Riccardo; Luconi, Ester; Biganzoli, Elia; Castaldi, Silvana (Acta Biomedica Atenei Parmensis, 2020)
The short paper present the problem of hospital acquired infection in subintensive units og a research and teaching hospital